Molecular mechanisms by which low doses of ionizing radiation promote neovascularization in ischemic tissues - Oliveira, Paula Alexandra Gomes de, 1981- (2018)
Tese de doutoramento, Ciências Biomédicas (Biologia Celular e Molecular), Universidade de Lisboa, Faculdade de Medicina, 2017